Accessibility Information on the Websites of New Zealand Luxury Lodges - Gillovic, Brielle; Harkison, Tracy (The School of Hospitality & Tourism, Auckland University of Technology, 2023)
This article reports on a wider study determining the provision of accessibility information by New Zealand Luxury Lodges. It presents important insights about the importance and role of the website provision of accessibility information for potential guests with disabilities, and the implications of this for accommodation providers.
Keywords: 35 Commerce, Management, Tourism and Services; 3506 Marketing